2013
DOI: 10.1007/s00284-013-0318-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Paenibacillus larvae Strains Isolated from Bulgarian Apiaries Based on Repetitive Element Polymerase Chain Reaction (Rep-PCR)

Abstract: The aim of the present study was to perform molecular typing of Paenibacillus larvae (P. larvae) isolates from Bulgarian apiaries with repetitive element polymerase chain reaction (rep-PCR) using BOX A1R, MBO REP1, and ERIC primers. A total of 96 isolates collected from brood combs with clinical symptoms of American foulbrood originating from apiaries located in different geographical regions of Bulgaria, a reference strain P. larvae NBIMCC 8478 and 30 commercial honey samples with Bulgarian origin were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Genersch et al (5) classified the strains LMG 16252 and DSM 3615 into two separate ERIC types, whereas Ebeling et al (24) categorized these strains as ERIC III/IV type according to MLST analysis. ERIC-PCR is known to exhibit limited reproducibility and inter-laboratory comparability (26). Based on the high genetic distance between this wgMLST clade and the remaining clades as well as the uncertainty regarding the ERIC types of both strains, the present data suggest this wgMLST clade may represent a novel ERIC type (or more than one ERIC type, as observed in ERIC III/IV clade) and should thus be further investigated and characterized.…”
Section: Population Structure Analysismentioning
confidence: 71%
“…Genersch et al (5) classified the strains LMG 16252 and DSM 3615 into two separate ERIC types, whereas Ebeling et al (24) categorized these strains as ERIC III/IV type according to MLST analysis. ERIC-PCR is known to exhibit limited reproducibility and inter-laboratory comparability (26). Based on the high genetic distance between this wgMLST clade and the remaining clades as well as the uncertainty regarding the ERIC types of both strains, the present data suggest this wgMLST clade may represent a novel ERIC type (or more than one ERIC type, as observed in ERIC III/IV clade) and should thus be further investigated and characterized.…”
Section: Population Structure Analysismentioning
confidence: 71%
“…Those affected by American Foulbrood were collected by tweezers, only if still alive; dead prepupae were discarded. AFB was confirmed by AFB Diagnostic Test Kit (Vita Europe Ltd) followed by P. larvae isolation and microscopic identification . Five bacterial colonies (A, B, C, D, and E) with typical P. larvae morphology obtained on TCBS agar were subjected to DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…The above typing schemes have been used to categorize crude patterns of P. larvae distribution in Europe (Genersch and Otten, 2003 ; Pentikäinen et al ., 2008 ; Loncaric et al ., 2009 ; Di Pinto et al ., 2011 ), the Americas (Alippi et al ., 2004 ; Antúnez et al ., 2007 ) and Australasia (Alippi et al ., 2004 ). However, rep-PCR methods have the disadvantage that they are difficult to repeat or to standardize between laboratories and therefore comparisons between different studies is difficult (Rusenova et al ., 2013 ). Recently, it was shown that the four ERIC genotypes can also be discriminated via matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (Schäfer et al ., 2014 ), providing a cost-effective, reliable and highly reproducible alternative tool for P. larvae ERIC typing.…”
Section: Introductionmentioning
confidence: 99%